Association of IL-33, IL1RL1 gene polymorphisms with serum IL-33 levels and risk of asthma in adults and asthmatic bronchitis in children (Chinese). Issue 5 (3rd September 2018) - Zhang, Guangyang; Lu, Jianjiang; Yin, Xiaowen; Sun, Yanyan; Li, Shanman
ABSTRACT: IL-33 binding to IL1RL1 is involved in asthma. The data show that involvement of the IL33/IL1RL1 genes in asthma is biologically plausible. The objective of this study was to investigate the association of IL33 and IL1R1 gene polymorphisms and serum IL-33 levels with asthma within the population of Xinjiang (China). A case group of 279 patients and 277 healthy controls were genotyped using the MassARRAY SNP genotyping system. In 113 asthma patients and 112 controls, the IL-33 levels were measured by enzyme linked immunosorbent assay (ELISA). The statistical analysis showed that IL-33 levels were associated with asthma and the rs16924159 (AA), rs1420102 (TT) genotype was associated with a significantly increased risk of asthma compared with the GG (rs16924159) or CC (rs1420102) genotypes. However, neither the rs13431828C/T genotypes, nor the rs928413 A/G genotypes were significantly associated with risk of asthma. In addition, the patients carrying the rs16924159 AA genotype presented with higher IL-33 levels compared to the GG group. This result suggested that the increase of IL-33 in patients with asthma may affect the expression level of serum IL-33. Furthermore, the rs16924159 G-A variant was associated with IL-33 levels in patients with asthma.